The Role of Job Analysis in the Development of Human Resources in Educational Institutions - Widyaningrum, Viranti (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Job analysis is a systematic process of identifying and documenting the responsibilities, duties, and qualifications required for each position in an organization. Through job analysis, educational institutions can formulate HR development strategies that are more effective and in line with the needs of educational institutions. This research aims to analyze the role of job analysis in the development of Human Resources (HR) in educational institutions. This research uses the Literature Review method by collecting data from journals, articles, books related to case studies that discuss several educational institutions that are accessed online. The research results show that job analysis has a significant contribution to training planning, career development and increasing employee competency. By conducting a good job analysis, educational institutions can ensure that human resource development runs in accordance with the institution's vision and mission. In addition, job analysis helps in preparing a clearer organizational structure and supports operational efficiency.